A single station ionospheric empirical model using GPS-TEC observations based on nonlinear least square estimation method. Issue 9 (1st November 2021) - Zhang, Bingbing; Niu, Jiqiang; Li, Wang; Shen, Yi; Wu, Tangting; Yang, Weifeng; Deng, Wenping
Abstract: This article presents a nonlinear least square estimation method based on the continuous TEC values at single stations from long-time recorded dual-frequency GPS data of International GNSS Service (IGS) stations to facilitate single-station empirical total electron content (TEC) modelling. The Nonlinear Polynomial GPS-TEC Model (NPGTM) at each of the four different stations (namely Ellesmere Island (alrt), Canada; Lhasa (lhaz), China; New Norcia (nnor), Australia; and East Ongle Island (syog) over the Antarctica) was constructed by the nonlinear least square estimation method using GPS-TEC data from 2005 to 2016 and validated with 2017–2018 datasets over the same locations in the dependencies of universal time (UT), solar activity (PI index), geomagnetic activity (Ap index) and day of year (DOY). The model was designed for quiet and moderate geomagnetic conditions (i.e. Ap ≤ 30 and F10.7 ≤ 160 sfu). Compared with IRI-2016 model values in 2017 to 2018, the accuracy of NPGTM model values is improved by 132% in high latitude area, 84% in medium latitude area and 88% in low latitude area. Evaluation results show that the NPGTM model values are in good agreement with GPS-TEC observations in high, medium and low latitude regions, which is much better than the IRI-2016 model values.